2011
DOI: 10.1088/0268-1242/26/8/085010
|View full text |Cite
|
Sign up to set email alerts
|

Metalorganic chemical vapor deposition growth and thermal stability of the AlInN/GaN high electron mobility transistor structure

Abstract: The Al x In 1−x N barrier high electron mobility transistor (HEMT) structure has been optimized with varied barrier composition and thickness grown by metalorganic chemical vapor deposition. After optimization, a transistor structure comprising a 7 nm thick nearly lattice-matched Al 0.83 In 0.17 N barrier exhibits a sheet electron density of 2.0 × 10 13 cm −2 with a high electron mobility of 1540 cm 2 V −1 s −1 . An Al 0.83 In 0.17 N barrier HEMT device with 1 μm gate length provides a current density of 1.0 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The literature survey reveals that the post-deposition annealing behavior of InAlN film has been rarely focused in the past. Only a few studies have reported the postdeposition annealing effects on the structural and electrical properties of In x Al 1-x N films [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey reveals that the post-deposition annealing behavior of InAlN film has been rarely focused in the past. Only a few studies have reported the postdeposition annealing effects on the structural and electrical properties of In x Al 1-x N films [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…33 Such superficial chemical variations can harm the quality of 2DEG density, decreasing also the electron mobility and the sheet carrier density when temperatures above 800 • C are employed. [34][35][36] On the basis of previous considerations, if we consider binary compounds separately, AlN is known to be stable up to 1250 • C, 37 whereas InN is known to be stable up to 550 • C [38][39][40] and decomposes above this temperature into N 2 and liquid In. Only few studies concern the chemical stability of InAlN layers through annealing temperatures.…”
mentioning
confidence: 99%
“…On the other hand, the postgrowth annealing of InAlN¯lm has barely been focused in the past due to di®erences in the thermal stabilities of InN and AlN. [15][16][17] Recently, our group studied the e®ects of post-deposition annealing temperatures (250-700 C) on the structural surface and optical properties of InAlN¯lms prepared using a magnetron co-sputtering technique. 17 The results obtained indicated a very small improvement in the crystallinity of InAlN¯lm after annealing at 500 C, however, crystalline quality of the¯lm was signi¯cantly improved at 700 C.…”
Section: Introductionmentioning
confidence: 99%